Exploring the Uniqueness of Nias Culinary Tourism: Creating Authentic Experiences Through the Perspective of Experiential Consumption - Febryola Indra; Nova Bernedeta Sitorus; Rachel Audrey Lano (Poltanesa, 2025)
Culinary tourism is increasingly popular, particularly in Indonesia, that is known for its rich cultural and culinary diversity. Nias Regency, renowned for its natural beauty and unique culture, offers distinctive dishes such as deer satay, grilled fish, and Nias fried rice. This study aims to explore the uniqueness of Nias's culinary offerings and how they reflect the region’s culture and traditions. It also examines how Experiential Consumption theory applies to creating authentic tourist experiences through local cuisine. Through a qualitative method by combining approaches such as in-depth interviews, direct observations, and literature review, this research identifies key elements that enhance authentic culinary tourism. The analysis integrates various theories, including Foodscapes, Cultural Proximity, Maslow’s Hierarchy of Needs, Authenticity, and Economic Impact. Additionally, Nias’s culinary scene not only enriches visitors’ experiences through food and cultural interaction but also promotes understanding of local values. It supports sustainable community development by empowering MSMEs and promoting local products. The findings highlight the significant potential of Nias's culinary tourism in contributing to Sustainable Development Goals (SDGs), particularly in areas such as poverty reduction (SDG 1), decent work and economic growth (SDG 8), responsible consumption and production (SDG 12), and sustainable partnerships (SDG 17). To optimize this potential, a comprehensive strategy focusing on culinary authenticity, community participation, and stakeholder collaboration is essential to position culinary tourism as a powerful tool for cultural promotion and regional economic growth.